Evaluation of an enzyme-linked immunospot assay for the immunodiagnosis of atypical spinal tuberculosis (atypical clinical presentation/atypical radiographic presentation) in China - Yuan, Kai; Zhong, Zhao-ming; Zhang, Qiang; Xu, Shu-chai; Chen, Jian-ting (The Brazilian journal of infectious diseases, 2013)
Atypical spinal tuberculosis (TB) usually presents in a slowly indolent manner with nonspecific clinical presentations making the diagnosis a great challenge for physicians. New technologies for the detection of atypical spinal TB are urgently needed. The aim of this study was to assess the diagnostic value of an enzyme-linked immunospot (ELISPOT) assay in clinically suspected cases of atypical spinal TB in China. From March 2011 to September 2012, a total of 65 patients with suspected atypical spinal TB were enrolled. In addition to conventional tests for TB, we used ELISPOT assays to measure the IFN-γ response to ESAT-6 and CFP-10 in T-cells in samples of peripheral blood mononuclear cells. Patients with suspected atypical spinal TB were classified by diagnostic category. Data on clinical characteristics of the patients and conventional laboratory results were collected. Out of 65 patients, 4 were excluded from the study. 18 (29.5%) subjects had culture-confirmed TB, 11 (18.0%) subjects had probable TB, and the remaining 32 (52.5%) subjects did not have TB. Generally, the features of atypical spinal TB include the following aspects: (1) worm-eaten destruction of vertebral endplate; (2) destruction of centricity of the vertebral body or concentric collapse of vertebral body; (3) tuberculous abscess with no identifiable osseous lesion; (4) contiguous or skipped vertebral body destruction. 26 patients with atypical spinal TB had available biopsy or surgical specimens for histopathologic examination and 23 (88.5%) specimens had pathologic features consistent with TB infection. The sensitivities of the PPD skin test and ELISPOT assay for atypical spinal TB were 58.6% and 82.8%, and their specificities were 59.4% and 81.3%, respectively. Malnutrition and age were associated with ELISPOT positivity in atypical spinal TB patients. The ELISPOT assay is a useful adjunct to current tests for diagnosis of atypical spinal TB.